The decision uncertainty toolkit: Risk measures and visual outputs to support decision making during public health crises - Megan Wiggins; Marie Varughese; Ellen Rafferty; Sasha van Katwyk; Christopher McCabe; Jeff Round; Erin Kirwin (PLoS ONE, 2025)
Background During public health crises such as the COVID-19 pandemic, decision-makers relied on infectious disease models to evaluate policy options. Often, there is a high degree of uncertainty in the evidence base underpinning these models. When there is increased uncertainty, the risk of selecting a policy option that does not align with the intended policy objective also increases; we term this decision risk. Even when models adequately capture uncertainty, the tools used to communicate their outcomes, underlying uncertainty, and associated decision risk have often been insufficient. Our aim is to support infectious disease modellers and decision-makers in interpreting and communicating decision risk when evaluating multiple policy options. Methods We developed the Decision Uncertainty Toolkit by adapting methods from health economics and infectious disease modelling to improve the interpretation and communication of uncertainty. Specifically, we developed a quantitative measure of decision risk as well as a suite of risk visualizations. We refined the toolkit contents based on feedback from early dissemination through conferences and workshops. Results The Decision Uncertainty Toolkit: (i) adapts and extends existing health economics methods for characterization, estimation, and communication of uncertainty to infectious disease modelling, (ii) introduces a novel risk measure that quantitatively captures the downside risk of policy alternatives, (iii) provides visual outputs for dissemination and communication of uncertainty and decision risk, and (iv) includes instructions on how to use the toolkit, standard text descriptions and examples for each component. The use of the toolkit is demonstrated through a hypothetical example. Conclusion The Decision Uncertainty Toolkit improves existing methods for communicating infectious disease model results by providing additional information regarding uncertainty and decision risk associated with policy alternatives. This empowers decision-makers to consider and evaluate decision risk more effectively when making policy decisions. Improved understanding of decision risk can improve outcomes in future public health crises.